Optimizing Waste Storage Areas in Health Care Centers - Parada-Daza, V (Springer, 2020)
Waste management is a critical issue for public health care services. Although operations management provides several tools for completing some stages of this process, the definition of a storage policy and the optimal packing of boxes with sharps waste in a storage area of a health care center are particular problems of high complexity. In this paper, a two-stage approach is proposed: The first stage considers the subproblem associated with the selection of the best policy. The second stage addresses the issue of waste packaging optimization. The multicriteria aspect of the first stage is addressed using the analytic hierarchy process, whereas the optimization of waste packaging is conducted using two heuristic methods: a sorting heuristic and the simulated annealing method. The best alternative method that is identified for the storage area considers the establishment of a specific room that is intended for the temporary storage of sharps waste. Furthermore, both heuristic methods provide suitable waste packaging options. The results suggest that the most appropriate method for each health care center must be selected by considering the order and sizes of the packing boxes, the required computational time and the required packaging efficiency. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.